Al-Khriet Agricultural Waste Adsorbent, for Removal Lead and Cadmium Ion from Aqueous Solutions - Maha H. Al-Hassani (Al-Khwarizmi College of Engineering – University of Baghdad, 2013)
The availability of low- cost adsorbent namely Al-Khriet ( a substance found in the legs of Typha Domingensis) as an agricultural waste material, for the removal of lead and cadmium from aqueous solution was investigated. In the batch tests experimental parameters were studied, including adsorbent dosage between (0.2-1) g, initial metal ions concentration between (50-200) ppm (single and binary) and contact time (1/2-6) h. The removal percentage of each ion onto Al-Khriet reached equilibrium in about 4 hours. The highest adsorption capacity was for lead (96%) while for cadmium it was (90%) with 50 ppm ions concentration, 1 g dosage of adsorbent and pH 5.5. Adsorption capacity in the binary mixture were reduce at about 8% for lead and 12 % for cadmium, which was attributed to competitive adsorption. The adsorption parameters were analyzed using both the Freundlich and Langmuir. Al-Khriet was best fitted by the Freundlich isotherm comparing with Langmuir model, and the rate constant was found to be 1.305 and 0.621 ((mg/g)(L/mg)1/n) for lead and cadmium respectively , while the kinetic of adsorption obeyed a second order rate equation and the rate constants were found to be (0.0161) for lead and ( 0.0125) mg.g-1.min-1 for cadmium.